Designing drug trials for Alzheimer's disease: What we have learned from the release of the phase III antibody trials: A report from the EU/US/CTAD Task Force. Issue 4 (1st July 2013) - Vellas, Bruno; Carrillo, Maria C.; Sampaio, Cristina; Brashear, H. Robert; Siemers, Eric; Hampel, Harald; Schneider, Lon S.; Weiner, Michael; Doody, Rachelle; Khachaturian, Zaven; Cedarbaum, Jesse; Grundman, Michael; et al.
Abstract: An international task force of investigators from academia, industry, nonprofit foundations, and regulatory agencies met in Monte Carlo, Monaco, on October 31, 2012, to review lessons learned from the recent bapineuzumab and solanezumab trials, and to incorporate insights gained from these trials into future clinical studies. Although there is broad consensus that Alzheimer's disease (AD) should be treated during its earliest stages, the concept of secondary prevention has evolved to be described more accurately as treatment of preclinical, presymptomatic, or early AD. There continues to be a strong emphasis on biomarkers and a need for new biomarkers; however, there has also been a realization, based on completed trials, that the most reliable indicator of clinical efficacy across the entire spectrum of disease from asymptomatic to AD dementia is likely a measure of cognition. The task force made many recommendations that should improve the likelihood of success in future trials, including larger phase 2 or combined phase 2/phase 3 studies, clear evidence of target engagement in the central nervous system, evidence of downstream effects on biomarkers before initiating phase 3 studies, consideration of adaptive and targeted trial designs, and use of sensitive measures of cognition as the most robust indicator of treatment benefit.